Stability Guaranteed Active Fault-Tolerant Control of Networked Control Systems - Shanbin Li; Dominique Sauter; Christophe Aubrun; Joseph Yamé (Journal of Control Science and Engineering)
The stability guaranteed active fault-tolerant control against actuators failures and plant uncertainties in networked control systems (NCSs) is addressed. A detailed design procedure is formulated as a convex optimization problem which can be efficiently solved by existing software. An illustrative example is given to show the efficiency of the proposed method for network-based control for uncertain systems.